Weak Ferromagnetic Property and Electromagnetic Waves Absorption Characteristic of La(1-x)BaxMnO3 (International Journal of Engineering Materials and Manufacture, 2019)
The weak ferromagnetic property and the electromagnetic waves absorption characteristic of La(1-x)BaxMnO3 (LBMO) compounds have been investigated. The samples of LBMO that are LaMnO3 (S0), La0.9Ba0.1MnO3 (S1); La0.8Ba0.2MnO3 (S2); and La0.7Ba0.3MnO3 (S3) were synthesized using high energy milling (HEM) method. Samples were characterized by means of XRD (X-ray diffractometer), HRPD (high-resolution powder neutron diffractometer), EDS (energy dispersive X-ray spectroscopy, VSM (vibrating sample magnetometer), and VNA (vector network analyzer). There is no magnetic ordering of ferromagnetic in S1 and S2 samples due to the Ba occupation factors of both less than 0.2. The Ba content in the S3 sample is greater than 0.2, hence the ferromagnetic property of the compound is not so visible with the VSM as well as the VNA. The absorption characteristics of electromagnetic waves using VNA indicated that there is an absorption of EM waves in the frequency range between 8-12 GHz with almost the same peak frequency for all four samples at 10.8 GHz with the absorption of around 5 dB. The existence of a weak ferromagnetic property can be detected clearly using HRPD. Neutron diffraction as a probe can observe the magnetic structure accurately even in a material having a weak ferromagnetic property.